Inventory Management and Performance of National Water and Sewerage Corporation Mbale City - Nabagega Caroline (Uganda Christian University, 2024)
This study examined the relationship between inventory management and performance of NWSC Mbale City. The specific objectives of the study were: to examine the relationship between inventory planning and performance of NWSC; to establish the relationship between inventory replenishment through procurement and performance of NWSC; to determine the relationship between inventory control and performance of NWSC. The study adopted a cross sectional study design. The findings indicated that there was a positive relationship between inventory planning and performance NWSC. This implies that improved inventory planning shall contribute to improved performance of NWSC in Uganda. The findings also indicated that there was a positive relationship between inventory replenishment and performance of NWSC implying that improved inventory replenishment shall contribute to improved performance in NWSC. Lastly, the findings indicated that there was a positive relationship between inventory control and performance of NWSC in Uganda, implying that improved inventory control shall contribute to improved performance of NWSC Mbale City. NWSC in Uganda should invest more money in ICT for inventory planning and hire experts on inventory planning to guide them on how to develop feasible inventory plans appropriate to the organization.